Comparison of FAP scores with the use of safety footwear and regular walking shoes. (2nd November 2017) - Benjamin, Daniel; Ahram, Tareq; De Ru, Esther; Choukou, Mohamed Amine; Abdi, Ellie; Gardan, Nicolas; Boyer, François Constant; Regnault, Philippe; Taiar, Redha
ABSTRACT: Gait analysis has been used for the assessment of gait-related disabilities and to provide detailed information. The gait characteristics of a healthy adult population have often been utilised to evaluate and monitor a subject's walk and patterns. This paper summarises a study that aims to compare the Functional Ambulation Performance (FAP) scores in male subjects wearing safety shoes versus regular walking shoes (RWS). Participants walked with RWS along the GAITRite® electronic walkway 30 times in self-selected speed and were analysed by the FAP; the subjects then repeated the same procedure with safety footwear. The data were then gathered in test groups containing 15 measured walks enabling the research team to establish an accurate and average FAP score for each test group. A descriptive statistic for the collected data was performed to determine the gait variables of the FAP score. Walking velocity, step and stride length, step and stride time, and step width among other measures were collected by the GAITRite® system and analysed in this research. Results show a slightly lower FAP score for test subjects walking with safety footwear and the parameters mainly affected were the step length and the stride length.